Graphics' design work: product / Nuur Ainul Najlaa' Brahim - Brahim, Nuur Ainul Najlaa' (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Laksa Ambal Sarawak faces limited recognition, which impedes its broader appeal. By employing attractive graphic design plans, deploying creative ads and social media strategies to narrate its distinctive tale and traditional crafting, these can help Laksa Ambal Sarawak to receive larger attention. Moreover, recruiting influencers to promote the products, and utilizing online platforms, will assist in cultivating well-established brands, transcending the awareness challenge, and fostering broader enjoyment.